Medicare Public Use Files and Alzheimer's disease factors in 2008 and 2010. (2013)
A new set of files are available to researchers as free downloads and they contain nonidentifiable claim-specific information for Fee-for-Service (FFS) Medicare beneficia- ries. Data on use and payments per beneficiary for Part A, B, and D are available for Alzheimer’s disorders and 10 other chronic conditions, allowing for novel comparisons.